Restoration dynamics and driving mechanisms of plateau mountain ecosystems under seismic disturbance: a case study of the Ludian M6.5 earthquake - Huang, Xin; Cao, Yanbo; Peng, Shuangyun; Luo, Maohao; Li, Siyang; Xu, Yufan; Liu, Jing (Frontiers in Ecology and Evolution, 2025)
IntroductionPlateau mountain ecosystems are highly sensitive to seismic disturbances due to their complex topography and fragile ecological environment. However, existing research still lacks a systematic understanding of the spatiotemporal dynamics and underlying driving mechanisms of ecosystem recovery in such regions following strong earthquakes. Thus, further in-depth investigation is urgently needed.MethodsThis study employed the 2014 Ludian M6.5 earthquake in Yunnan, China, as a case study. Using the Remote Sensing Ecological Index (RSEI) derived from Landsat imagery, we quantitatively assessed ecological disturbance and recovery over nearly a decade. The Geodetector model was applied to identify key driving factors of ecological quality changes.Results(1) Disturbance effects: the earthquake caused a significant short-term decline of 21.3% in the mean RSEI of the affected area, with the degree of degradation intensifying alongside seismic intensity. (2) Recovery dynamics: the ecosystem exhibited a three-stage nonlinear evolution pattern of “rapid recovery – steady recovery – stable surpassing.” By 2021, approximately 91% of the region had experienced ecological quality improvement, while 8.75% of the area still showed degradation, mainly concentrated in zones with intensive human activities. (3) Driving mechanisms: before the earthquake, the ecological pattern was primarily governed by natural background factors such as climate and soil; after the earthquake, aspect became the dominant factor reshaping the ecological pattern; and during the recovery period, the driving mechanisms presented a composite feature characterized by the persistent influence of the topography–climate system combined with the progressively increasing role of human interventions.DiscussionThe findings revealed the complex interplay between seismic disturbance, topographic constraints, and human activities in shaping ecological recovery patterns in plateau mountain regions. The study provides a theoretical basis and practical insights for post-disaster ecological restoration and sustainable management in seismically active mountainous areas.